11th hour - Patterson, James (New York : Grand Central Publishing, 2012)
When millionaire Chaz Smith is mercilessly gunned down, Lindsay Boxer discovers that the murder weapon is linked to the deaths of four of San Francisco's most untouchable criminals. Then she's called next to the most bizarre crime scene she's ever witnessed: two bodiless heads elaborately displayed in the garden of a world-famous actor.
Keywords: Women detectives; Public prosecutors; Crimes against -- Fiction